ANALISIS KESULITAN BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA PADA MATERI STATISTIKA - Soraya Djamilah; Rahmi Hidayati; Ikrima Ikrima (EMTEKA: Jurnal Pendidikan Matematika, 2023)
This study aims to describe the analysis of students' learning difficulties in mathematics on statistics material. This research is a type of qualitative descriptive research with data collection methods in the form of online tests which are carried out by giving test sheets to 26 students from class VIII C of SMPN 4 Sungai Tabuk. The results of the research conducted showed that students experienced difficulties on statistical material, were in mathematical modeling, concepts, calculation errors, and make a conclusion.